2022
DOI: 10.35912/ijfam.v4i2.835
|View full text |Cite
|
Sign up to set email alerts
|

Personal Financial Management Skills Of University Students and Their Financial Experiences During The Covid-19 Pandemic

Abstract: Purpose: The main purpose of this study was to assess university students’ financial management skills and their financial experiences during the Covid-19 pandemic. Research methodology: The research adopted the explanatory sequential mixed methods research design where a survey of 181 students on work-related learning was conducted using questionnaires and qualitative interviews. Data were analyzed using IBM SPSS Statistic 27 Results: The study established that the majority of the students do not have a bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…However, women indicated that apart from saving in monetary terms, because of hyperinflation, they were saving by converting local currency into United States Dollars and saving the money in a wallet or by buying physical assets that can be turned into cash easily. The results concur with Gumbo et al (2022) who established that university students in Zimbabwe do not save and usually run out of money before receiving the next income.…”
Section: Savingsupporting
confidence: 89%
“…However, women indicated that apart from saving in monetary terms, because of hyperinflation, they were saving by converting local currency into United States Dollars and saving the money in a wallet or by buying physical assets that can be turned into cash easily. The results concur with Gumbo et al (2022) who established that university students in Zimbabwe do not save and usually run out of money before receiving the next income.…”
Section: Savingsupporting
confidence: 89%
“…Students' decisions are also impacted by the counsel of friends or family who work in finance, as well as their own prior experience. Research from Gumbo et al, (2022) revealed that the main expenses for university students include food, housing, clothes, petrol, technology, gadgets, transportation, entertainment, and alcohol. On that note, students regularly make financial decisions that will affect how they manage their personal finances in the future.…”
Section: Table 6: Financial Management In Decision Makingmentioning
confidence: 99%
“…Although dismantling educational institutions has proven effective, the Pandemic has caused difficulties for several stakeholders and society at large (Owusu-Fordjour, Koomson, Hanson, 2020). The study from Gumbo et al, (2022) found that most students do not have a budget or think they can budget mentally without adequately accounting for all monthly expenses, run out of money before. Today's students frequently worry about debt or student loans, application fees, rent housing costs, books, study materials, student job loss, anxieties about their future financial situation, future education, and future careers (Gutiérrez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, companies are facing dual effects and problems with the pressure to engage in environmental activities (Anoke, Onu, & Agagbo, 2022;Buniamin, Alrazi, Johari, & Rahman, 2011;Hawlader, Rana, Kalam, & Polas, 2021;Qiu, Shaukat, & Tharyan, 2016) and development (El Fallahi, Ibenrissoul, & Adil, 2022;Kooli, lock Son, & Beloufa, 2022). Industrial development helps the nation realize a sustainable economy, although it negatively affects the environment (Gumbo et al, 2022;Isaifan and Kooli, 2022). Therefore, balanced development is required through green industry, production, and growth to balance this relationship.…”
Section: Introductionmentioning
confidence: 99%